Metal-organic frame material separation membrane and its manufacturing method and application
Patent Information
- Application Number
- JP2023523255
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-15
- Filing Date
- 2020-10-28
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-10-28
Smart Images

Figure 0007642065000021 
Figure 0007642065000022 
Figure 0007642065000023
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal-organic framework material separation membrane and a manufacturing method thereof, which belongs to the technical field of manufacturing organic gas separation membranes. [Background technology]
[0002] Gas membrane separation technology is a new technology that utilizes the efficient selective permeability of membrane materials to organic matter to separate organic matter from the main gas phase, and has the advantages of continuous process, no heat generation, no secondary pollution, high recovery rate, low energy consumption and compact size. It is currently the mainstream technology for organic matter separation and volatile organic compounds (VOCs) treatment in developed countries, and is widely used in the fields of environmental protection, chemical industry and biopharmaceuticals.
[0003] Most of the conventional organic gas separation membranes are manufactured through the coating and crosslinking process of siloxane, of which polydimethylsiloxane (PDMS) is the most widely used. Block copolymer (PEBA) is also a common functional layer material for organic gas separation membranes, which has two properties: the hardness of polyamide (PA) material and the softness of polyether (PE) material. The soft polyether provides high permeability and allows organic substances to permeate preferentially. The hard polyamide provides mechanical strength and overcomes the membrane swelling caused by excessive adsorption of organic substances, thereby maintaining good permeation selectivity. Current PDMS membranes have a large flux, but their molecular structure is loose and difficult to adjust and control, so their separation factor is low and it is difficult to improve the selectivity for specific substances. PEBA membranes have the properties of two types of block molecules, but their molecular composition is fixed, their structure is single, and they are generally dense. They have a high separation factor but a small overall flux, which limits their application.
[0004] As people's early perception of membranes, "sieving mechanism" membranes strictly control the pore size of the membrane pores, allowing only molecules smaller than the pore size of the membrane pores to pass through and blocking macromolecules, thereby realizing material separation, and therefore its flux is large and the separation factor is high. However, since the diameter of most gas molecules is smaller than 1 nanometer and the difference in molecular diameter between gas molecules is small, the requirements for the membrane structure are extremely high to achieve accurate sieving. At present, gas separation membranes using sieving mechanism have not been commercialized.
[0005] Metal-organic framework materials (MOFs) are a new type of porous material that has been developed in recent years. They have the advantages of adjustable pore size, high specific surface area, stable structure, and easy functional modification, making them a research hotspot for researchers at home and abroad. In the field of separation processes, metal-organic framework materials, as a new adsorbent, show a wide range of potential applications in the areas of organic matter separation, ion removal from water, and concentration analysis. However, they are only used as an adsorption process, and have problems such as the process being discontinuous and requiring analysis, the adsorbent being difficult to regenerate, and the service life being short.
[0006] Patent CN110052185A discloses a modification method based on dopamine UiO-66 membrane. The method involves vertically immersing a porous substrate in a fixed frame into a precursor solution prepared by dissolving zirconium chloride and terephthalic acid in N,N-dimethylformamide, and heat-treating under constant temperature conditions for 48-96h. Ultrasonic treatment is performed for 3-30s to obtain a substrate with seed crystals. The substrate with deposited seed crystals is heat-treated at least twice in the same manner as above, and stopped until a continuous UiO-66 membrane is obtained. The obtained membrane is first immersed and then immersed again to obtain a dopamine-grafted UiO-66 membrane. There is almost no mutually embedded UiO-66 structure in the dopamine-grafted UiO-66 membrane, so the membrane is less dense and difficult to improve selectivity for specific substances. Summary of the Invention
[0007] The object of the present invention is to solve the problems of the conventional technology that it is difficult to obtain a continuous and complete MOFs separation functional layer, or the bonding between the separation functional layer and the undercoat is not firm and is prone to fall off and defects, the resulting separation membrane has a small flux, a low separation factor, and is difficult to improve the selectivity for specific substances, and the manufacturing process is discontinuous, and to construct a metal-organic framework material separation functional layer with a continuous and mutually embedded structure by carrying out a specific pretreatment on the undercoat and combining the method of in-situ growth reaction, to manufacture a membrane surface functional layer with a special micro-geometry, and to realize the adjustment control of its structure and chemical composition. At the same time, in addition to the functional layer, a coating and a protective layer are formed to fill the defects that may appear on the functional layer, to prevent the functional layer from being contaminated and destroyed during use, and to improve the separation factor and service life of the separation membrane. At the same time, the separation membrane surface has a larger surface roughness and hydrophobicity, and obtains a stronger anti-contamination ability, which is conducive to the contact, dissolution and permeation of material molecules with the membrane surface, thereby improving the flux of the membrane.
[0008] According to a first aspect of the present invention, there is provided a MOFs separation membrane comprising an undercoat film and a MOFs functional layer, the structure of the MOFs functional layer including a plurality of mutually embedded polyhedral structures.
[0009] The mutually embedded polyhedral structures described in the present invention refer to a structure in which a portion of a polyhedron is inserted inside another polyhedral structure adjacent to or close to it, or a polyhedron shares a portion of a crystal lattice with one or more surrounding polyhedra.
[0010] According to some embodiments of the present invention, the polyhedrons are composed of a plurality of crystal lattices, and two adjacent polyhedra in the mutually embedded polyhedral structure share a crystal lattice.
[0011] According to some embodiments of the present invention, the distance between the centers of two adjacent polyhedrons in the mutually embedded polyhedral structure is smaller than the average length L of the two adjacent polyhedrons, preferably smaller than 0.95L, more preferably 0.2-0.9L.
[0012] In the present invention, the “average value L” refers to half the sum of the lengths of two polyhedrons. For example, if the length of polyhedron A is L1 and the length of polyhedron B is L2, then L=(L1+L2) / 2.
[0013] According to some embodiments of the invention, at least 20% of the polyhedra in the MOFs functional layer are embedded in one another, preferably at least 30%, preferably at least 40%, preferably at least 50%, preferably at least 60%, preferably at least 80% of the polyhedra are embedded in one another.
[0014] According to some embodiments of the invention, the polyhedrons comprise hexahedral and / or octahedral structures.
[0015] According to some embodiments of the invention, the length of the polyhedron is 50-2000 nm.
[0016] According to some embodiments of the present invention, the polyhedron is composed of a plurality of crystal lattices, wherein the crystal lattices are composed of metal atoms and organic ligands.
[0017] According to a preferred embodiment of the present invention, the metal atom is a zirconium atom. , 2 The atom is selected from an obium atom, a molybdenum atom, and a cobalt atom.
[0018] According to a preferred embodiment of the invention, said organic ligand is selected from terephthalic acid or nitroterephthalic acid.
[0019] According to some embodiments of the invention, the length of the hexahedrons is 50-1000 nm, wherein the proportion of hexahedrons with a length of 400-600 nm is 50-80%.
[0020] According to some embodiments of the invention, the length of the octahedra is 200-2000 nm, wherein the proportion of octahedra having a length of 800-1200 nm is 60-80%.
[0021] The "length of a polyhedron" according to the present invention refers to the maximum length between the vertices of the polyhedron.
[0022] According to some embodiments of the present invention, each of the octahedra or hexahedrons is composed of a plurality of crystal lattices formed by a plurality of pairs of zirconium metal atoms and terephthalic acid.
[0023] According to some embodiments of the invention, the MOFs functional layer comprises one or more layers of inter-embedded polyhedral structures.
[0024] According to some embodiments of the present invention, the MOF s machine The pore size of the active layer is determined by the metal atoms and the organic Ligand The average size of the crystal lattice formed is determined by the average size of the crystal lattice formed by
[0025] According to some embodiments of the present invention, the average pore size of the MOFs functional layer is 0.1-2.0 nm, preferably 0.30-0.96 nm.
[0026] According to some embodiments of the invention, the thickness of the MOFs functional layer is 200-5000 nm.
[0027] According to some embodiments of the invention, the thickness of the MOFs functional layer is 1000-5000 nm.
[0028] According to some embodiments of the present invention, the undercoat film is one or more selected from a polypropylene film, a polyethylene film, a polyvinyl chloride film, or a polytetrafluoroethylene film.
[0029] According to some embodiments of the present invention, the pore size of the undercoat membrane is 10-10000 nm, preferably 50-5000 nm, more preferably 200-1000 nm.
[0030] In some preferred embodiments of the present invention, the undercoat membrane is a polypropylene membrane, a polyethylene membrane, a polyvinyl chloride membrane, or a polytetrafluoroethylene membrane with a pore size of 50 nm-5000 nm, produced by melt spin-drawing or thermally induced phase separation.
[0031] According to some embodiments of the present invention, the MOFs functional layer further comprises an auxiliary functional layer.
[0032] According to some embodiments of the present invention, the auxiliary functional layer is a part that repairs any areas that may exist that are not completely formed into the buried octahedron or buried hexahedron structure.
[0033] According to some embodiments of the present invention, the organosilicon layer is a surface of the MOFs functional layer. On the surface Located It is an organosilicon layer .
[0034] According to a second aspect of the present invention, (1) preparing a solution containing a first organic solvent, an organic ligand, a first metal compound, and an auxiliary selected from water or glacial acetic acid; (2) pretreating the undercoat film and introducing metal atoms from the first metal compound in step (1) onto the undercoat film; (3) mixing the base film pretreated in step (2) with the solution in step (1) to obtain a first mixture, and heating and reacting the first mixture to obtain a MOFs separation membrane; (4) optionally, a step of washing the separation membrane to obtain the resulting membrane.
[0035] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent, the organic ligand, and the first metal compound is (10-1000):(1-100):(1-100).
[0036] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent, the organic ligand, and the first metal compound is (100-1000):(1-10):(1-10).
[0037] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent, the organic ligand, and the first metal compound is (100-700):1:1, such as 100:1:1, 200:1:1, 250:1:1, 300:1:1, 350:1:1, 420:1:1, 450:1:1, 550:1:1, 610:1:1, 650:1:1, and any value therebetween.
[0038] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent, the organic ligand, and the first metal compound is (400-600):1:1.
[0039] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent to the auxiliary water is 100:(0.00 1 -0.05), for example 100:0.0 1 prong is 100:0.03.
[0040] According to a preferred embodiment of the present invention, water is employed as an auxiliary agent in step (1), and the functional layer of the prepared metal-organic framework material comprises a plurality of octahedral structures embedded with each other.
[0041] According to some embodiments of the present invention, in step (1), the molar ratio of the first organic solvent to the auxiliary glacial acetic acid is 100:(20-60), such as 100:25, 100:30, 100:40, or 100:50.
[0042] According to a preferred embodiment of the present invention, glacial acetic acid is employed as an assistant in step (1), and the functional layer of the prepared metal-organic framework material comprises a plurality of hexahedral structures embedded in each other.
[0043] According to some embodiments of the present invention, the first organic solvent is one or more selected from N-methylpyrrolidone, N,N-dimethylformamide, and dimethylacetamide.
[0044] According to some embodiments of the present invention, the organic ligand is selected from terephthalic acid and / or nitroterephthalic acid.
[0045] According to some embodiments of the present invention, the first metal compound is one or more selected from zirconium compounds, niobium compounds, molybdenum compounds, and cobalt compounds, and is preferably zirconium tetrachloride.
[0046] According to some embodiments of the present invention, the undercoat film is one or more selected from a polypropylene film, a polyethylene film, a polyvinyl chloride film, or a polytetrafluoroethylene film.
[0047] According to some embodiments of the present invention, the pore size of the undercoat membrane is 10-10000 nm, preferably 50-5000 nm, more preferably 200-1000 nm.
[0048] In some preferred embodiments of the present invention, the undercoat membrane is a polypropylene membrane, a polyethylene membrane, a polyvinyl chloride membrane, or a polytetrafluoroethylene membrane with a pore size of 50 nm-5000 nm, produced by melt spin-drawing or thermally induced phase separation.
[0049] According to some embodiments of the present invention, the step (2) comprises: (2A-1) preparing a solution containing polyacrylic acid, polyvinyl alcohol and a second metal compound; (2A-2) applying the solution of step (2A-1) to the undercoat.
[0050] According to some embodiments of the invention, the polyacrylic acid includes polyacrylic acid and partially hydrolyzed polyacrylic acid.
[0051] According to some embodiments of the present invention, the mass concentration of polyacrylic acid and polyvinyl alcohol in the solution in step (2A-1) is 500-2000 mg / L.
[0052] According to some embodiments of the present invention, the molar ratio of the sum of the polyacrylic acid and polyvinyl alcohol to the metal compound in the solution of step (2A-1) is 1-3:1.
[0053] According to some embodiments of the present invention, the metal atom in the second metal compound is the same as the metal atom in the first metal compound in step (1), and preferably the second metal compound is one or more selected from zirconium compounds, niobium compounds, molybdenum compounds and cobalt compounds, preferably zirconium tetrachloride.
[0054] According to some embodiments of the present invention, in step (2A-2), the ratio of the surface area of the undercoat film to the volume of the solution obtained in step (2A-1) is 0.1-10 m 2 / L, for example, 0.8m 2 / L, 1.2m 2 / L, 1.5m 2 / L, 1.7m 2 / L, 2.3m 2 / L, 2.5m 2 / L, 2.7m 2 / L, 3.0m 2 / L, 3.5m 2 / L, 4.0m 2 / L, 4.5m 2 / L, 5.0m 2 / L, 5.5m 2 / L, 6.0m 2 / L, 6.5m 2 / L, 7.0m 2 / L, 7.5m 2 / L, 8.0m 2 / L, 8.5m 2 / L, 9.0m 2 / L, 9.5m 2 / L, and any value therebetween.
[0055] According to some embodiments of the present invention, in step (2A-2), the ratio of the surface area of the undercoat film to the volume of the solution obtained in step (2A-1) is 0.5-5 m 2 / L.
[0056] In some preferred embodiments of the present invention, in step (2A-2), the ratio of the surface area of the undercoat film to the volume of the solution obtained in step (2A-1) is 1-2 m 2 / L.
[0057] In some preferred embodiments of the present invention, the step (2) specifically comprises: (a) mixing polyacrylic acid having a mass concentration of 1000 mg / L, partially hydrolyzed polyacrylic acid, polyvinyl alcohol and zirconium tetrachloride in a molar ratio of 2:1, stirring for 1 h, and then obtaining a mixed solution; (b) applying the solution produced in (a) onto the surface of the undercoat film and then drying it to deposit a certain amount of metal atoms onto the surface of the undercoat film.
[0058] According to some embodiments of the present invention, the step (2) comprises: (2B-1) preparing a solution containing a metal complex represented by formula I and a second organic solvent; (2B-2) mixing the undercoat film with the solution of step (2B-1); (2B-3) using a third solvent to wash the base film after mixing in step (2B-2).
[0059] [ka]
[0060] In formula I, Q is selected from an amide group, a carbonyl group, or a C1-C6 alkylene group; R1 is selected from hydrogen, a C1-C6 alkyl group, a C1-C6 alkoxy group, or a halogen; M1 is the same as the metal atom in the first metal compound in step (1), preferably M1 is selected from a zirconium atom, a niobium atom, a molybdenum atom, or a cobalt atom; m is 5-20; and n is 1-10.
[0061] According to some embodiments of the present invention, in formula I, Q is selected from an amide group, R1 is selected from a C3-C6 alkyl group, m is 5-20, and n is 1-10.
[0062] According to some embodiments of the present invention, the metal complexes shown in formula I are as follows:
[0063] [ka]
[0064] According to some embodiments of the present invention, the metal complexes shown in formula I are as follows:
[0065] [ka]
[0066] According to some embodiments of the present invention, the second organic solvent is one or more selected from organic solvents that can swell the undercoat film, preferably selected from C5-C10 aliphatic hydrocarbons, C1-C10 halogenated aliphatic hydrocarbons, C6-C20 aromatic hydrocarbons, and C6-C20 halogenated aromatic hydrocarbons, more preferably one or more selected from n-pentane, n-hexane, chloroform, carbon tetrachloride, benzene, and toluene.
[0067] According to some embodiments of the present invention, the third solvent is one or more selected from solvents capable of de-swelling the swollen base film, and is preferably selected from water.
[0068] According to some embodiments of the present invention, in the solution of step (2B-1), the mass concentration of the metal complex of formula I is 500-2000 mg / L.
[0069] According to some embodiments of the present invention, in step (2B-2), the ratio of the surface area of the undercoat film to the volume of the solution obtained in step (2B-1) is 0.1-10 m 2 / L, for example, 0.8m 2 / L, 1.2m 2 / L, 1.5m 2 / L, 1.7m 2 / L, 2.3m 2 / L, 2.5m 2 / L, 2.7m 2 / L, 3.0m 2 / L, 3.5m 2 / L, 4.0m 2 / L, 4.5m 2 / L, 5.0m 2 / L, 5.5m 2 / L, 6.0m 2 / L, 6.5m 2 / L, 7.0m 2 / L, 7.5m 2 / L, 8.0m 2 / L, 8.5m 2 / L, 9.0m 2 / L, 9.5m 2 / L, and any value therebetween.
[0070] According to some embodiments of the present invention, in step (2B-2), the ratio of the surface area of the undercoat film to the volume of the solution obtained in step (2B-1) is 0.5-5 m 2 / L.
[0071] In some preferred embodiments of the present invention, in step (2B-2), the ratio of the surface area of the undercoat film to the volume of the solution obtained in step (2B-1) is 1-2 m2 / L.
[0072] In some preferred embodiments of the present invention, the step (2) specifically comprises: (a) dissolving acrylic acid-N-tert-butylacrylamide / zirconium complex in n-hexane and dissolving in a solvent at a mass concentration of 1000 mg / L to prepare a homogeneous solution; (b) immersing the undercoat in the solution of step (a) for 1-24 hours, then quickly transferring and washing the undercoat in deionized water, and then removing and drying to obtain a modified undercoat, during which some of the acrylic acid-N-tert-butylacrylamide / zirconium complexes are embedded in the surface layer of the embedded undercoat structure, introducing a certain amount of stable zirconium atoms into the undercoat.
[0073] [ka]
[0074] According to some embodiments of the present invention, the step (2) comprises: (2C-1) preparing a solution containing a metal complex represented by formula II; (2C-2) mixing the undercoat film with the solution of step (2C-1) to obtain a mixture, and polymerizing the mixture under microwave radiation conditions.
[0075] [ka]
[0076] In Formula II, X is selected from an amide group, a carbonyl group, or a C1-C6 alkylene group; R2, R3, and R4 are the same or different and each independently selected from a hydrogen, a C1-C6 alkyl group, a C1-C6 alkoxy group, or a halogen; M2 is the same as the metal atom in the first metal compound in step (1), and preferably M2 is selected from a zirconium atom, a niobium atom, a molybdenum atom, or a cobalt atom.
[0077] According to some embodiments of the present invention, in formula II, X is selected from an amide group, and R2, R3 and R4 are the same or different and are each independently selected from hydrogen, a C1-C3 alkyl group.
[0078] According to some embodiments of the present invention, the metal complex shown in formula II is:
[0079] [ka]
[0080] According to some embodiments of the present invention, the metal complex shown in formula II is:
[0081] [ka]
[0082] According to some embodiments of the present invention, the solution of the metal complex in step (2C-1) is an aqueous solution of the metal complex.
[0083] According to some embodiments of the present invention, in the solution of step (2C-1), the mass concentration of the metal complex of formula II is 500-20000 mg / L.
[0084] According to some embodiments of the present invention, in step (2C-2), the ratio of the surface area of the undercoat film to the volume of the solution obtained in step (2C-1) is 0.1-10 m 2 / L, for example, 0.8m 2 / L, 1.2m 2 / L, 1.5m 2 / L, 1.7m 2 / L, 2.3m 2 / L, 2.5m 2 / L, 2.7m 2 / L, 3.0m 2 / L, 3.5m 2 / L, 4.0m 2 / L, 4.5m2 / L, 5.0m 2 / L, 5.5m 2 / L, 6.0m 2 / L, 6.5m 2 / L, 7.0m 2 / L, 7.5m 2 / L, 8.0m 2 / L, 8.5m 2 / L, 9.0m 2 / L, 9.5m 2 / L, and any value therebetween.
[0085] According to some embodiments of the present invention, in step (2C-2), the ratio of the surface area of the undercoat film to the volume of the solution obtained in step (2C-1) is 0.5-5 m 2 / L.
[0086] According to some preferred embodiments of the present invention, in step (2C-2), the ratio of the surface area of the undercoat film to the volume of the solution obtained in step (2C-1) is 1-2 m 2 / L.
[0087] According to some embodiments of the present invention, in step (2C-2), the microwave intensity of the microwave radiation is 500-2000 μW / cm 2 It is.
[0088] According to some embodiments of the present invention, in step (2C-2), the microwave frequency of the microwave radiation is 1000-200000 Hz.
[0089] In some preferred embodiments of the present invention, the step (2) specifically comprises: (a) dissolving an acrylic acid-N-dipropenyl enamine / zirconium complex in an aqueous solution to prepare a graft polymerization liquid; (b) immersing the undercoat film in the graft polymerization solution prepared in step (a); (c) performing radiation-induced graft polymerization under microwave radiation of a certain intensity to generate a graft polymerization reaction between the methyl-generated radicals on the undercoat film and the double bonds in the acrylic acid-N-dipropenyl enamine / zirconium complex in the graft polymerization solution, thereby obtaining a modified undercoat film and introducing zirconium atoms onto the surface.
[0090] [ka]
[0091] In the present invention, after the undercoat film is pretreated, metal atoms can be introduced into the undercoat film on the one hand, and MOFs Functional Layer On the other hand, the metal atoms introduced into the underlayer are used to form MOFs by subsequent in-situ growth. Functional Layer can provide metal nodes for the formation of MOFs Functional Layer During the growth process, an embedded structure appears, thus avoiding the occurrence of defects.
[0092] According to some embodiments of the present invention, in step (3), the ratio of the surface area of the undercoat film after the pretreatment in step (2) to the volume of the solution obtained in step (1) is (0.01-100) m 2 / L, preferably (0.01-10)m 2 / L, more preferably 0.5-2m 2 / L.
[0093] According to a preferred embodiment of the present invention, in step (3), before the base film is added to the solution obtained in step (1), it can be subjected to the following treatment: the surface of the base film (or the membrane module produced) is washed with water and an organic solvent in sequence, and then dried, the organic solvent is preferably ethanol, methanol or acetone, and preferably the base film (or the membrane module produced) is washed twice with water, washed twice with an organic solvent and then dried.
[0094] According to some embodiments of the present invention, step (3) comprises: The first mixture is heated to react with the organic ligand and the metal compound to produce an MOFs material on the surface of the base film, thereby obtaining the separation film.
[0095] According to a preferred embodiment of the present invention, in step (3), the reaction temperature is 50-300°C, preferably, the reaction temperature is 100-200°C.
[0096] According to a preferred embodiment of the present invention, in the step (3), the reaction pressure is 0.01-0.5 MPa (gauge pressure), preferably, the reaction pressure is 0.05-0.1 MPa (gauge pressure).
[0097] According to a preferred embodiment of the present invention, in step (3), the reaction time is 1-100 h, such as 5 h, 17 h, 20 h, 25 h, 27 h, 30 h, 40 h, 50 h, 60 h, 70 h, 80 h, 90 h, and any value therebetween.
[0098] According to a preferred embodiment of the present invention, in step (3), the reaction time is 10-72 hours, preferably 15-30 hours.
[0099] According to a preferred embodiment of the present invention, the step (3) can be carried out under an inert gas atmosphere, and preferably the inert gas is nitrogen gas.
[0100] According to some embodiments of the present invention, in step (4), the separation membrane is taken out (or the polymerization solution in the membrane module is discharged), and the membrane surface after polymerization is washed multiple times with an organic solvent and water to remove not completely reacted monomers and solvent, to obtain a MOFs organic gas separation membrane (or membrane module), in which the organic solvent for washing the membrane surface includes ethanol, methanol or acetone, and preferably, the separation membrane is washed twice with water and twice with an organic solvent and then dried.
[0101] According to some embodiments of the present invention, the method for producing a MOFs separation membrane of the present invention further comprises: (5) A step of performing a repair treatment once or a plurality of times on the MOFs separation membrane obtained in the step (3) or (4), preferably comprising the steps of: (A) mixing the MOFs separation membrane with a solution containing a first organic solvent, an organic ligand, a first metal compound, and an auxiliary selected from water or glacial acetic acid to obtain a second mixture; (B) heating the second mixture and reacting it to obtain a MOFs separation membrane; (C) optionally, subjecting the separation membrane to a washing treatment to obtain the separation membrane.
[0102] According to some embodiments of the present invention, step (A) comprises: (A1) preparing a solution containing a first organic solvent, an organic ligand, a first metal compound, and an auxiliary selected from water or glacial acetic acid; (A2) adding the MOFs separation membrane obtained in step (2) or (3) to the solution obtained in step (A1) to obtain a second mixture.
[0103] According to a preferred embodiment of the present invention, the molar ratio of the first organic solvent, the organic ligand and the first metal compound in step (A) is (10-1000):(1-100):(1-100), preferably (100-1000):(1-10):(1-10), more preferably (100-700):1:1, such as 100:1:1, 200:1:1, 250:1:1, 300:1:1, 350:1:1, 400:1:1, 420:1:1, 550:1:1 or 600:1:1, 650:1:1 and any value therebetween.
[0104] According to a preferred embodiment of the present invention, in step (A), the molar ratio of the first organic solvent to the auxiliary water is 100:(0.00 1 -0.05), for example 100:0.0 1 prong is 100:0.03.
[0105] According to a preferred embodiment of the present invention, in step (A), the molar ratio of the first organic solvent to the auxiliary glacial acetic acid is 100:(20-60), such as 100:25, 100:30, 100:40 or 100:50.
[0106] According to a preferred embodiment of the present invention, in step (A2), the ratio of the surface area of the MOFs separation membrane to the volume of the solution in step (A1) is (0.01-100) m 2 / L, preferably (0.01-10)m 2 / L, more preferably 1m 2 / L.
[0107] According to a preferred embodiment of the present invention, the step (B) comprises: and heating the second mixture to react the organic ligand with the first metal compound and continue to generate a MOFs material on the surface of the MOFs organic gas separation membrane.
[0108] According to a preferred embodiment of the present invention, in step (B), the reaction temperature is 50-300° C., the reaction pressure is 0.01-0.5 MPa (gauge pressure), and the reaction time is 1-100 h.
[0109] According to a preferred embodiment of the present invention, in step (B), the reaction temperature is 100-200° C., the reaction pressure is 0.05-0.1 MPa (gauge pressure), and the reaction time is 5-50 h.
[0110] According to a preferred embodiment of the present invention, in step (B), the reaction time is 10-20 h.
[0111] According to a preferred embodiment of the present invention, the step (B) can be carried out under an inert gas atmosphere, and preferably the inert gas is nitrogen gas.
[0112] According to some embodiments of the present invention, in step (C), the separation membrane is taken out (or the polymerization solution in the membrane module is discharged), and the membrane surface after polymerization is washed multiple times with an organic solvent and water to remove not completely reacted monomers and solvent, to obtain a MOFs organic gas separation membrane (or membrane module), in which the organic solvent for washing the membrane surface includes ethanol, methanol or acetone, and preferably, the separation membrane is washed twice with water and twice with an organic solvent and then dried.
[0113] According to some embodiments of the present invention, the method for producing the MOFs separation membrane of the present invention further includes a step of applying a silane coating solution to the surface of the MOFs separation membrane produced in step (3) or (4) or (B) or (C) and heating the MOFs separation membrane coated with the silane coating solution to cause a crosslinking reaction in the silane coating solution, thereby producing a MOFs separation membrane including an organosilicon layer.
[0114] According to some embodiments of the present invention, the silane coating solution is applied to the surface of the MOFs separation membrane prepared in step (4) or step (C) by a method such as dip coating or blade coating, thereby coating the surface of the MOFs separation membrane with the silane coating solution to a thickness of 1-100 microns, preferably 25 microns.
[0115] According to some embodiments of the present invention, the temperature of the crosslinking reaction is 50-300°C, preferably 50-200°C, more preferably 150°C, and the time is 0.1-20h, preferably 0.1-10h, more preferably 0.5h.
[0116] Crosslinking reaction Afterwards, a cross-linked silane protective layer was formed on the surface of the MOFs organic gas separation membrane.
[0117] According to some embodiments of the present invention, the preparation of the silane coating solution includes: Mixing and dissolving S1, silane, a crosslinking agent, and an organic solvent to obtain a mixed solution; S2, adding a catalyst to the mixed solution to perform pre-crosslinking thereon to obtain a silane coating solution.
[0118] According to some embodiments of the present invention, in step S1, the ratio of silane, crosslinker and organic solvent is (0.1-10):(0.1-10):(90-100), preferably (1-10):(1-10):(90-100), more preferably 9:1:90.
[0119] According to a preferred embodiment of the present invention, the silane may be a monomer of siloxane material, including one or more of dimethylsiloxane, cured silicone rubber, and sulfurized silicone rubber mixed in any ratio; and / or the crosslinker includes tetraethyl orthosilicate or tetramethoxysilane; and / or the organic solvent includes at least one of heptane, pentane, toluene, benzene, xylene, and hexane, preferably n-hexane.
[0120] According to a preferred embodiment of the present invention, the catalyst can be an organotin catalyst such as dibutyltin dilaurate or a titanium complex catalyst such as tetrabutyl titanate. The amount of the catalyst used is 0.01-1 wt%, preferably 0.01-0.1 wt%.
[0121] According to some embodiments of the present invention, the time of pre-crosslinking in step S2 is 1-48 h, preferably 10-30 h, more preferably 24 h, and / or the viscosity of the silane coating solution is 100-50000 mPa s, preferably 100-5000 mPa s, more preferably 2000 mPa s.
[0122] According to some embodiments of the present invention, the method for producing the MOFs separation membrane of the present invention further comprises the following steps. The produced MOFs separation membrane is treated with an alkaline solution to adjust the pore size. The adjustment process breaks the chemical bonds between some of the zirconium atoms and organic matter, increasing the permeability of the functional layer and the penetrability of the internal crystal lattice, thereby obtaining the desired separation pore size and more suitable flux.
[0123] According to some embodiments of the present invention, the alkaline solution is preferably a sodium hydroxide solution with a pH of 9-13. The addition process is accompanied by stirring, and the flow rate obtained by stirring is 0.01-1 m / s, preferably 0.1 m / s. The time is 10-120 min, preferably 30-60 min.
[0124] According to a third aspect of the present invention, there is provided a MOFs separation membrane produced by the method for producing a MOFs separation membrane according to the second aspect.
[0125] According to a fourth aspect of the present invention, there is provided an application of the MOFs separation membrane according to the first aspect or the MOFs separation membrane produced by the method according to the second aspect in organic separation.
[0126] According to some embodiments of the present invention, the MOFs separation membrane can be used for benzene-based organic compounds such as benzene, toluene, and xylene.
[0127] According to some embodiments of the present invention, the MOFs separation membrane can be used to separate alkanes such as methane, ethane, propane, butane, pentane, hexane, heptane, cyclohexane, and isopentane, and unsaturated alkane gases such as ethylene, propylene, acetylene, butene, and styrene, and their volatile gases, from nitrogen gas and air.
[0128] According to some embodiments of the present invention, the separation may be a single or multi-stage membrane separation.
[0129] According to some embodiments of the present invention, in the purification and separation of helium gas, the MOFs separation membrane can be used in conjunction with cryogenic, dehydrogenation, and deoxygenation processes.
[0130] According to some embodiments of the present invention, the MOFs separation membrane can be used in conjunction with cryogenics, rectification and PSA in the separation of olefinic alkane.
[0131] According to some embodiments of the present invention, in the field of organic gas separation, the MOFs separation membrane can carry out a set of technologically developed processes such as condensation, adsorption, and absorption.
[0132] Compared with the conventional techniques, the MOFs separation membrane and the preparation method of the MOFs separation membrane provided by the present invention have the following advantages:
[0133] (1) The manufacturing process is simple, the operation is easy, and the cost is low.
[0134] (2) The fabricated MOFs functional layer has excellent resistance to chemical dissolution, high temperature resistance, and high mechanical strength.
[0135] (3) In the MOFs functional layer, the polyhedrons are embedded in each other and spread over the surface of the underlying membrane, which is dense and continuous, has a small thickness, and a uniform pore size distribution, so that the membrane has a large flux and a high separation factor.
[0136] (4) The organosilicon protective layer is hydrophobic and breathable, preventing damage to the MOFs functional layer by water vapor and particulate matter.
[0137] (5) The method according to the present invention can be used to prepare a high-performance organic gas separation membrane, which has the above-mentioned excellent properties and can be effectively used in the fields of petrochemistry, biology, medicine, energy, environmental protection and so on. [Brief description of the drawings]
[0138] [Figure 1] 1 shows an electron microscope image of the surface of the MOFs organic gas separation membrane produced in Example 1. [Diagram 2] 1 shows an electron microscope image of the surface of the MOFs organic gas separation membrane produced in Example 5. [Diagram 3]1 shows an electron microscope image of the surface of the MOFs organic gas separation membrane produced in Example 9. [Figure 4] 1 shows an electron microscope image of the surface of the MOFs organic gas separation membrane produced in Example 13. [Diagram 5] 2 shows an electron microscope image of the surface of the MOFs organic gas separation membrane produced in Example 21. [Figure 6] 1 is a photograph of a polyvinylidene fluoride (PVDF) substrate in Comparative Example 1 after immersion in a precursor solution. [Figure 7] 1 is a photograph of a polyvinylidene fluoride (PVDF) substrate in Comparative Example 2 after immersion in a precursor solution. [Figure 8] 1 shows an electron microscope image of the surface of the MOFs organic gas separation membrane produced in Comparative Example 3. [Figure 9] 1 shows an electron microscope image of the surface of the MOFs organic gas separation membrane produced in Comparative Example 4. [Figure 10] 1 shows a schematic diagram of a membrane performance test device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0139] The present invention will be further described below with reference to examples, but is not limited to these examples.
[0140] Unless otherwise stated, all raw materials used in the examples are commercially available, and all chemicals referred to are chemicals common to the art, unless otherwise stated.
[0141] (1) The structural formula of the acrylic acid-N-tert-butylacrylamide / zirconium complex in the examples is as follows:
[0142] [ka]
[0143] Preparation method: 47g acrylic acid is weighed and dissolved in 250g deionized water, and the pH value is adjusted to 7-9 with NaOH solution. Take 50g deionized water, add 12g sodium dodecyl sulfate (SDS) and 8.9g nonylphenol ethoxylate (NP), and add 3g t-butylacrylamide monomer dropwise while continuing to stir uniformly to form a uniform, stable and clear solution. After mixing the two solutions, they are put into an insulated polymerization kettle, and nitrogen gas is introduced to remove oxygen for about 10 minutes, and then the redox initiator ammonium persulfate-sodium hydrogen sulfite (0.05g of the two reagents are prepared in 1% deionized water and added) is added, and after the solution becomes viscous, the aeration is stopped and the reaction is allowed to naturally rise in temperature. After 6-8 hours, the reaction is completed, and the product hydrogel is sheared, dried at 50℃, and crushed to obtain acrylic acid-t-butylacrylamide copolymer. The copolymer is dissolved in water at a certain concentration, and a zirconium acetate salt is added to obtain the polyacrylic acid complex zirconium-t-butylacrylamide copolymer.
[0144] (2) The structural formula of the acrylic acid-N-dipropenyl enamine / zirconium complex in the examples is as follows:
[0145] [ka]
[0146] Preparation method: Weigh out 120g acrylic acid and dissolve it in 80g deionized water, and adjust the pH value to 7-9 with NaOH solution. Take 20 deionized water and add 6g methylenebisacrylamide to form a uniform, stable and clear solution. Take 95g industrial 5# white oil, add appropriate amount of 7.65g Span80 and 10g Tween80, and stir to form a stable uniform solution. Mix the first part of the water phase and the oil phase, emulsify with an emulsifier to form a stable reverse phase emulsion, and place in a polymerization kettle to cool. First, add ammonium persulfate initiator solution, and prepare 0.05g ammonium persulfate in 1% deionized water solution. While stirring uniformly and introducing nitrogen gas for protection, gradually drop sodium hydrogen sulfite solution (0.05g pure solid is prepared in 1% deionized water solution) and the second part of methylenebisacrylamide solution. The reaction has a slight exothermic phenomenon. After the dropwise addition is completed, the stirring is continued for 2 hours. The emulsion is then taken out and isopropanol / acetone is poured into it to produce a white precipitate. The precipitate is centrifuged and washed with ethanol to obtain a copolymer of acrylic acid and methylenebisacrylamide. The copolymer is dissolved in water and zirconium acetate is added to obtain the copolymer.
[0147] Test Method The analytical method described in the literature (Research on organic vapor / nitrogen gas separation system of hollow fiber composite membrane, He Chunhong, Tianjin University, 2005) was used to conduct membrane separation performance tests for nitrogen gas / organic vapor mixed gas. The test equipment is as shown in Figure 10.
[0148] A typical structure of a gas separation membrane is a very thin dense layer coated on a porous support. The actual thickness of the dense layer is difficult to measure accurately, so the permeability coefficient and the effective thickness of the membrane are always used in combination, and their ratio is called the permeation rate and is calculated by the following formula:
[0149]
number
[0150] In the above formula, J i is the permeation rate of gas component i, and its unit is mol / (m 2 s Pa). P is the permeability coefficient of gas i component, with units of mol m / (m 2 s Pa). l is the effective thickness of the film, in m. Q i is the molar flow rate of component i in the permeating gas under standard conditions, with the unit being mol / s. Δp is the permeating pressure difference, with the unit being Pa. A is the membrane area, with the unit being m 2 It is.
[0151] The separation factor α is calculated by the following formula:
[0152]
number
[0153] [Example 1] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water are mixed in a molar ratio of 400:1:1:0.01 and thoroughly stirred to obtain a solution necessary for producing a MOFs membrane.
[0154] (2) Pretreatment of the base film (a) Polyacrylic acid having a mass concentration of 1000 mg / L, partially hydrolyzed polyacrylic acid, polyvinyl alcohol, and zirconium tetrachloride are mixed in a molar ratio of 2:1, and stirred for 1 hour to obtain a post-reaction solution.
[0155] (b) A polypropylene hollow fiber substrate having a pore size of 500 nm was washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) was 1 m 2 The solution produced in (a) is applied to the surface of the dried base film so that the amount of zirconium atoms is 1 / L (i.e., 1 L of the manufacturing solution described in step (a) is applied to a film with a surface of 1 square meter), and then dried to deposit a certain amount of zirconium atoms on the surface of the base film, resulting in a pretreated base film.
[0156] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1) The pretreated base film is immersed in the MOFs production solution described in 2. above to obtain a first mixture, which is protected by introducing nitrogen gas, and an in-situ growth reaction is carried out at 120°C for 24 hours to obtain a separation membrane.
[0157] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0158] (5) The separation membrane obtained in step (4) is washed to obtain a MOFs organic gas separation membrane. The electron microscope image of the surface of the prepared film is shown in Figure 1. As can be seen from Figure 1, the MOFs functional layer of the prepared film is composed of octahedral crystals embedded in each other, which spread across the surface of the base film, are dense and continuous, have high surface roughness, the base film is completely covered, and there are few defects in the functional layer.
[0159] The performance test data of the membrane is shown in Table 1. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 4.828 x 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 0.301×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 16.03.
[0160] [Example 2] The difference from Example 1 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) is 0.1 m 2 All that is required is to apply the solution produced in (a) to the surface of the dried base film so that the volume of the preparation solution described in step (a) is 1 / L (i.e., 1 L of the preparation solution described in step (a) is applied to a film with a surface of 0.1 square meter).
[0161] The performance test data of the membrane is shown in Table 1. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 2.01 x 10 -6 mol / (m 2 ·s·Pa), whereas the flux of propylene gas is 0.18×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 11.17.
[0162] [Example 3] The difference from Example 1 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) is 5m 2 All that is required is to apply the solution produced in (a) to the surface of the dried base membrane so that the resulting solution is 1 / L (i.e., 1 L of the manufacturing solution described in step (a) is applied to a membrane with a surface of 5 square meters).
[0163] The performance test data of the membrane is shown in Table 1. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 10.41 x 10 -6 mol / (m 2 ·s·Pa), whereas the flux of propylene gas is 1.206×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 8.63.
[0164] [Example 4] The difference from Example 1 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) is 10 m 2 All that is required is to apply the solution produced in (a) to the surface of the dried base membrane so that the total volume is 1 / L (i.e., 1 L of the manufacturing solution described in step (a) is applied to a membrane with a surface of 10 square meters).
[0165] The performance test data of the membrane is shown in Table 1. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 17.733 x 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 1.909×10 -6 mol / (m 2 ·s·Pa), indicating that the nitrogen gas / propylene separation factor is 9.29.
[0166] [Table 1]
[0167] [Example 5] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water are mixed in a molar ratio of 400:1:1:0.01 and thoroughly stirred to obtain a solution necessary for producing a MOFs membrane.
[0168] (2) Pretreatment of the base film (a) Acrylic acid-N-tert-butylacrylamide / zirconium complex is dissolved in n-hexane to prepare a homogeneous solution at a mass concentration of 1000 mg / L.
[0169] (b) A polypropylene hollow fiber substrate having a pore size of 500 nm was washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) was 1 m 2 The dried base film is immersed in the manufacturing solution described in (a) for 2 hours so that the total volume becomes 1 / L (i.e., a film with a surface of 1 square meter is placed in 1 L of the manufacturing solution described in step (a)), and after being taken out, it is quickly transferred into deionized water for washing, and after being taken out and dried, a modified base film is obtained, during which some of the acrylic acid-N-tert-butylacrylamide / zirconium complexes are embedded in the surface layer of the embedded base film structure, introducing a certain amount and stable zirconium atoms into the base film.
[0170] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1) The pretreated base film is immersed in the MOFs production solution described in 2. above to obtain a first mixture, which is then protected by introducing nitrogen gas and subjected to an in-situ growth reaction at 200°C for 24 hours to obtain a separation membrane.
[0171] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0172] (5) The separation membrane obtained in step (4) is washed to obtain a MOFs organic gas separation membrane.
[0173] An electron microscope image of the surface of the produced membrane is shown in FIG.
[0174] The performance test data of the membrane is shown in Table 2. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 1.521 x 10 -6 mol / (m 2 ·s·Pa), whereas the flux of propylene gas is 0.088×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 17.28.
[0175] [Example 6] The difference from Example 5 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 0.1 m 2 All that is required is to immerse the dried base membrane in the manufacturing solution described in (a) so that the surface area is 0.1 m2 / L (i.e. a membrane surface of 0.1 m2 is placed in 1 L of the manufacturing solution described in step (a)).
[0176] The performance test data of the membrane is shown in Table 2. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 1.01 x 10 -6 mol / (m 2 ·s·Pa), whereas the propylene gas flux is 0.12×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 8.42.
[0177] [Example 7] The difference from Example 5 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 5m 2 All that is required is to immerse the dried base membrane in the manufacturing solution described in (a) so that the surface area is 1 / L (i.e. a membrane with a surface of 5 square meters is placed in 1 L of the manufacturing solution described in step (a)).
[0178] The performance test data of the membrane is shown in Table 2. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 2.89 × 10 -6 mol / (m 2 ·s·Pa), whereas the flux of propylene gas is 0.188×10 -6 mol / (m 2 This indicates that the nitrogen gas / propylene separation factor is 15.37.
[0179] [Example 8] The difference from Example 5 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 10 m 2 All that is required is to immerse the dried base membrane in the manufacturing solution described in (a) so that the surface area is 1 / L (i.e. a membrane with a surface of 10 square meters is placed in 1 L of the manufacturing solution described in step (a)).
[0180] The performance test data of the membrane is shown in Table 2. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 3.50 × 10 -6 mol / (m 2 ·s·Pa), whereas the flux of propylene gas is 0.215×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 16.28.
[0181] [Table 2]
[0182] [Example 9] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water are mixed in a molar ratio of 100:1:1:0.001 and thoroughly stirred to obtain a solution necessary for producing a MOFs membrane.
[0183] (2) Pretreatment of the base film (a) An acrylic acid-N-dipropenyl enamine / zirconium complex is dissolved in a solution, and then dissolved in water at a mass concentration of 1000 mg / L to prepare a graft polymerization solution.
[0184] (b) A polypropylene hollow fiber substrate having a pore size of 500 nm was washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) was 1 m 2 / L (i.e., a film with a surface area of 1 square meter is placed in 1 L of the manufacturing solution described in step (a)), and 2 Radiation graft polymerization was carried out for 2 hours using microwave radiation with an intensity frequency of 1000-200,000 Hz, generating a graft polymerization reaction between the methyl group-generated radicals on the polypropylene microporous membrane and the double bonds in the acrylic acid-N-dipropenyl enamine / zirconium complex in the graft polymerization solution, thereby obtaining a modified base membrane and introducing zirconium atoms onto the surface.
[0185] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1) The pretreated base film is immersed in the MOFs production solution described in 2. above to obtain a first mixture, which is then protected by introducing nitrogen gas and subjected to an in-situ growth reaction at 200°C for 24 hours to obtain a separation membrane.
[0186] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0187] (5) The separation membrane obtained in step (4) is washed to obtain a MOFs organic gas separation membrane.
[0188] An electron microscope image of the surface of the produced membrane is shown in FIG.
[0189] The performance test data of the membrane is shown in Table 3. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 1.41 × 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 0.047×10 -6 mol / (m 2 This indicates that the nitrogen gas / propylene separation factor is 30.00.
[0190] [Example 10] The difference from Example 9 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 0.1 m 2 The only thing that needs to be done is to immerse the dried base film in the manufacturing solution described in (a) so that the radiation-induced graft polymerization is carried out in a volume of 1 / L (i.e., a film with a surface of 0.1 square meters is placed in 1 L of the manufacturing solution described in step (a)).
[0191] The performance test data of the membrane is shown in Table 3. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 0.341 x 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 0.0114×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 29.91.
[0192] [Example 11] The difference from Example 9 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 5m 2 The only thing that needs to be done is to immerse the dried base membrane in the manufacturing solution described in (a) so that the radiation-induced graft polymerization is carried out in a volume of 1 / L (i.e., a membrane with a surface of 5 square meters is placed in 1 L of the manufacturing solution described in step (a)).
[0193] The performance test data of the membrane is shown in Table 3. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 1.884 × 10 -6 mol / (m 2 s Pa), whereas the flux of propylene gas is 0.074×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 25.46.
[0194] [Example 12] The difference from Example 9 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 10 m 2 The only thing that needs to be done is to immerse the dried base membrane in the manufacturing solution described in step (a) so that the radiation-induced graft polymerization is carried out in a volume of 1 / L (i.e., a membrane with a surface of 10 square meters is placed in 1 L of the manufacturing solution described in step (a)).
[0195] The performance test data of the membrane is shown in Table 3. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 2.984 × 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 0.121×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 24.66.
[0196] [Table 3]
[0197] [Example 13] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and glacial acetic acid are mixed in a molar ratio of 400:1:1:150 and thoroughly stirred to obtain a solution required for the preparation of MOFs membrane.
[0198] (2) Pretreatment of the base film (a) Polyacrylic acid having a mass concentration of 1000 mg / L, partially hydrolyzed polyacrylic acid, polyvinyl alcohol, and zirconium tetrachloride are mixed in a molar ratio of 2:1, and stirred for 1 hour to obtain a post-reaction solution.
[0199] (b) A polyethylene hollow fiber substrate having a pore size of 500 nm is washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) is 1 m 2 The solution produced in (a) is applied to the surface of the dried base film so that the solution becomes 1 / L (i.e., 1 L of the solution described in step (a) is applied to a film with a surface of 1 square meter), and then dried, thereby attaching a certain amount of zirconium atoms to the surface of the base film.
[0200] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1)The pretreated base film is immersed in the MOFs production solution described in 2. above to obtain a first mixture, which is then protected by introducing nitrogen gas and subjected to an in-situ growth reaction at 200°C for 24 hours to obtain a separation membrane.
[0201] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0202] (5) The separation membrane obtained in step (4) is washed to obtain a MOFs organic gas separation membrane.
[0203] An electron microscope image of the surface of the produced membrane is shown in FIG.
[0204] The performance test data of the membrane is shown in Table 4. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 0.896 x 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 0.047×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 19.06.
[0205] [Example 14] The difference from Example 13 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 0.1 m 2 All that is required is to apply the solution produced in (a) to the surface of the dried base film so that the volume of the preparation solution described in step (a) is 1 / L (i.e., 1 L of the preparation solution described in step (a) is applied to a film with a surface of 0.1 square meter).
[0206] The performance test data of the membrane is shown in Table 4. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 0.288 × 10 -6 mol / (m 2·s·Pa), whereas the propylene gas flux is 0.0095×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 30.32.
[0207] [Example 15] The difference from Example 13 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 5m 2 All that is required is to apply the solution produced in (a) to the surface of the dried base membrane so that the resulting solution is 1 / L (i.e., 1 L of the manufacturing solution described in step (a) is applied to a membrane with a surface of 5 square meters).
[0208] The performance test data of the membrane is shown in Table 4. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 1.208 × 10 -6 mol / (m 2 s Pa), whereas the flux of propylene gas is 0.1659×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 7.28.
[0209] [Example 16] The difference from Example 13 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 10 m 2 All that is required is to apply the solution produced in (a) to the surface of the dried base membrane so that the total volume is 1 / L (i.e., 1 L of the manufacturing solution described in step (a) is applied to a membrane with a surface of 10 square meters).
[0210] The performance test data of the membrane is shown in Table 4. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 1.48 × 10 -6 mol / (m 2 s Pa), whereas the flux of propylene gas is 0.2659×10 -6mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 5.57.
[0211] [Table 4]
[0212] [Example 17] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and glacial acetic acid are mixed in a molar ratio of 200:1:1:100 and thoroughly stirred to obtain a solution required for the preparation of MOFs membrane.
[0213] (2) Pretreatment of the base film (a) Acrylic acid-N-tert-butylacrylamide / zirconium complex is dissolved in n-hexane to prepare a homogeneous solution at a mass concentration of 1000 mg / L.
[0214] (b) A polyethylene hollow fiber substrate having a pore size of 500 nm is washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) is 10 m 2 The dried base film is immersed in the manufacturing solution described in (a) for 10 hours so that the total volume of the base film becomes 1 / L (i.e., a film with a surface of 10 square meters is placed in 1 L of the manufacturing solution described in step (a)), and after being taken out, it is quickly transferred into deionized water for washing, and after being taken out and dried, a modified base film is obtained, during which some of the acrylic acid-N-tert-butylacrylamide / zirconium complexes are embedded in the surface layer of the embedded base film structure, introducing a certain amount and stable zirconium atoms into the base film.
[0215] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1)The pretreated base film is immersed in the MOFs production solution described in 2. above to obtain a first mixture, which is then protected by introducing nitrogen gas and subjected to an in-situ growth reaction at 200°C for 24 hours to obtain a separation membrane.
[0216] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0217] (5) The separation membrane obtained in step (4) is washed to obtain a MOFs organic gas separation membrane.
[0218] The performance test data of the membrane is shown in Table 5. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 2.468 × 10 -6 mol / (m 2 ·s·Pa), whereas the propylene gas flux is 0.115×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 21.46.
[0219] [Example 18] The difference from Example 17 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 0.1 m 2 All that is required is to immerse the dried base membrane in the manufacturing solution described in (a) so that the surface area is 0.1 m2 / L (i.e. a membrane surface of 0.1 m2 is placed in 1 L of the manufacturing solution described in step (a)).
[0220] The performance test data of the membrane is shown in Table 5. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 0.3008 x 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 0.0184×10 -6 mol / (m 2This indicates that the nitrogen gas / propylene separation factor is 16.35.
[0221] [Example 19] The difference from Example 17 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 1 m 2 All that is required is to immerse the dried base membrane in the manufacturing solution described in (a) so that the surface area is 1 / L (i.e. 1 square meter of membrane is placed in 1 L of the manufacturing solution described in step (a)).
[0222] The performance test data of the membrane is shown in Table 5. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 1.241 × 10 -6 mol / (m 2 ·s·Pa), whereas the propylene gas flux is 0.038×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 32.66.
[0223] [Example 20] The difference from Example 17 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 5m 2 All that is required is to immerse the dried base membrane in the manufacturing solution described in (a) so that the surface area is 1 / L (i.e. a membrane with a surface of 5 square meters is placed in 1 L of the manufacturing solution described in step (a)).
[0224] The performance test data of the membrane is shown in Table 5. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 2.198 × 10 -6 mol / (m 2 ·s·Pa), whereas the flux of propylene gas is 0.087×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 25.26.
[0225] [Table 5]
[0226] [Example 21] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and glacial acetic acid are mixed in a molar ratio of 1000:1:1:500 and thoroughly stirred to obtain a solution required for the preparation of MOFs membrane.
[0227] (2) Pretreatment of the base film (a) An acrylic acid-N-dipropenyl enamine / zirconium complex is dissolved in a solution, and then dissolved in pure water at a mass concentration of 1000 mg / L to prepare a graft polymerization solution.
[0228] (b) A polyethylene hollow fiber substrate having a pore size of 500 nm is washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) is 1 m 2 / L (i.e., a film with a surface area of 1 square meter is placed in 1 L of the manufacturing solution described in step (a)), and 2 Radiation graft polymerization was carried out for 2 hours using microwave radiation with an intensity frequency of 1000-200,000 Hz, generating a graft polymerization reaction between the methyl group-generated radicals on the polypropylene microporous membrane and the double bonds in the acrylic acid-N-dipropenyl enamine / zirconium complex in the graft polymerization solution, thereby obtaining a modified base membrane and introducing zirconium atoms onto the surface.
[0229] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1) The pretreated base film is immersed in the MOFs production solution described in 2. above to obtain a first mixture, which is then protected by introducing nitrogen gas and subjected to an in-situ growth reaction at 200°C for 24 hours to obtain a separation membrane.
[0230] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0231] (5) The separation membrane obtained in step (4) is washed to obtain a MOFs organic gas separation membrane.
[0232] An electron microscope image of the surface of the produced membrane is shown in FIG.
[0233] The performance test data of the membrane is shown in Table 6. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 0.889 × 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 0.042×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 21.17.
[0234] [Example 22] The difference from Example 21 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 0.1 m 2 The only thing that needs to be done is to immerse the dried base film in the manufacturing solution described in (a) so that the radiation-induced graft polymerization is carried out in a volume of 1 / L (i.e., a film with a surface of 0.1 square meters is placed in 1 L of the manufacturing solution described in step (a)).
[0235] The performance test data of the membrane is shown in Table 6. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 0.152 × 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 0.0112×10 -6 mol / (m 2s·Pa), and the nitrogen gas / propylene separation factor is 13.57.
[0236] [Example 23] The difference from Example 21 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 5m 2 The only thing that needs to be done is to immerse the dried base membrane in the manufacturing solution described in (a) so that the radiation-induced graft polymerization is carried out in a volume of 1 / L (i.e., a membrane with a surface of 5 square meters is placed in 1 L of the manufacturing solution described in step (a)).
[0237] The performance test data of the membrane is shown in Table 6. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 1.055 × 10 -6 mol / (m 2 ·s·Pa), whereas the flux of propylene gas is 0.087×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 12.13.
[0238] [Example 24] The difference from Example 21 is that in the pretreatment of the undercoat film in step (2), the ratio of the surface area of the undercoat film to the solution described in (a) was 10 m 2 The only thing that needs to be done is to immerse the dried base membrane in the manufacturing solution described in (a) so that the radiation-induced graft polymerization is carried out in a volume of 1 / L (i.e., a membrane with a surface of 5 square meters is placed in 1 L of the manufacturing solution described in step (a)).
[0239] The performance test data of the membrane is shown in Table 6. The performance test data of the membrane is that in a mixture of propylene and nitrogen gas, the nitrogen gas flux at 0.1 MPa is 1.386 × 10 -6 mol / (m 2 s Pa), whereas the propylene gas flux is 0.114×10 -6 mol / (m 2s·Pa), and the nitrogen gas / propylene separation factor is 12.16.
[0240] [Table 6]
[0241] [Examples 25-29] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water were mixed in molar ratios of 50:1:1:0.0005, 100:1:1:0.001, 200:1:1:0.002, 500:1:1:0.005 and 1000:1:1:0.001 and thoroughly stirred to obtain a solution necessary for producing a MOFs membrane.
[0242] (2) Pretreatment of the base film (a) Polyacrylic acid having a mass concentration of 1000 mg / L, partially hydrolyzed polyacrylic acid, polyvinyl alcohol, and zirconium tetrachloride are mixed in a molar ratio of 2:1, and stirred for 1 hour to obtain a post-reaction solution.
[0243] (b) A polypropylene hollow fiber substrate having a pore size of 500 nm was washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) was 1 m 2 The solution produced in (a) is applied to the surface of the dried base film so that the amount of zirconium atoms is 1 / L (i.e., 1 L of the manufacturing solution described in step (a) is applied to a film with a surface of 1 square meter), and then dried, thereby attaching a certain amount of zirconium atoms to the surface of the base film.
[0244] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1) The pretreated base film is immersed in the MOFs production solution described in 2. above to obtain a first mixture, which is protected by introducing nitrogen gas, and an in-situ growth reaction is carried out at 120°C for 24 hours to obtain a separation membrane.
[0245] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0246] (5) The separation membrane obtained in step (4) is washed to obtain a MOFs organic gas separation membrane.
[0247] The separation coefficient and membrane flux tests for n-hexane gas and nitrogen gas were carried out on the separation membranes prepared in Examples 25-29. The performance test data of the membranes are shown in Table 7.
[0248] [Table 7]
[0249] As can be seen from the data in Table 7, with the decrease in the specific gravity (decrease in concentration) of the monomer content in the blended components, the separation factor of the produced separation membrane for nitrogen gas / n-hexane showed an increasing trend, increasing from 34 to 51, and the flux also improved slightly, reaching 1.5 × 10 -6 mol / (m 2 s Pa) to 3 × 10 -6 mol / (m 2 s·Pa). This is mainly due to the decrease in monomer concentration, the in-situ polymerization reaction becomes more regular, the functional layer structure formed becomes denser, the defects are fewer and the crystallinity is higher, which helps to improve the separation factor. When the monomer concentration is high, the reaction rate is fast and the ligand concentration is high, so it is easy to form oligomers and aggregation phenomenon, the crystal structure is loosened but the oligomers block the channel, and both the separation factor and flux are reduced. Working Example 29, that is, when the blending ratio is 1000:1:1:0.01, the separation factor drops sharply to less than 10, and the flux is 10×10 -6 mol / (m 2This indicates that if the monomer concentration is too low, many defects will occur in the MOFs functional layer, the flux will increase significantly, and the separation performance of the membrane cannot be maintained for a long time.
[0250] [Examples 30-37] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water are mixed in a molar ratio of 500:1:1:0.005 and thoroughly stirred to obtain a solution necessary for producing a MOFs membrane.
[0251] (2) Pretreatment of the base film (a) Polyacrylic acid having a mass concentration of 1000 mg / L, partially hydrolyzed polyacrylic acid, polyvinyl alcohol, and zirconium tetrachloride are mixed in a molar ratio of 2:1, and stirred for 1 hour to obtain a post-reaction solution.
[0252] (b) A polypropylene hollow fiber substrate having a pore size of 500 nm was washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) was 1 m 2 The solution produced in (a) is applied to the surface of the dried base film so that the amount of zirconium atoms is 1 / L (i.e., 1 L of the manufacturing solution described in step (a) is applied to a film with a surface of 1 square meter), and then dried, thereby attaching a certain amount of zirconium atoms to the surface of the base film.
[0253] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1) The pretreated base film is immersed in the MOFs manufacturing solution described in 3. above to obtain a first mixture, which is protected by introducing nitrogen gas, and the in-situ growth reaction is carried out at 120°C for 6 h, 12 h, 18 h, 24 h, 30 h, 36 h, 42 h, and 48 h to obtain a separation membrane.
[0254] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0255] (5) The separation membrane obtained in step (4) is washed to obtain a MOFs organic gas separation membrane.
[0256] The separation coefficient and membrane flux tests for n-hexane gas and nitrogen gas were carried out on the separation membranes prepared in Examples 30-37, and the performance test data of the membranes are shown in Table 8.
[0257] [Table 8]
[0258] As can be seen from the data in Table 8, when the reaction time increased from 12 to 24 h, the separation factor of the MOFs separation membrane increased rapidly from 30 to 50, indicating that the formation of the MOFs functional layer enabled the membrane to separate nitrogen gas / n-hexane. In addition, the gas permeation flux increased to 3.0×10 -6 mol / (m 2 The functional layer is made of UIO-66, which has a uniform pore size distribution and extremely high porosity, and its crystal lattice pore size is 0.6 nm, which is slightly smaller than the size of the n-hexane molecule, so the functional layer prevents the passage of n-hexane molecules, but the nitrogen molecule has a diameter of 3.4-3.6 nm and can pass through the MOFs membrane, resulting in a very high flux.
[0259] With further increase in reaction time, the separation factor stabilizes at 52, but the flux gradually decreases, and at 48 h reaction time, the flux is 1.5 × 10 -6 mol / (m 2The pressure in the membrane decreases to below 1.0×10 s·Pa. This indicates that the reaction can form a continuous and dense separation layer in 24 h. Further increasing the reaction time only increases the thickness of the functional layer, and some oligomers, monomers, and solvents are further enveloped in the functional layer and block the membrane pores, resulting in a decrease in the permeation flux. Therefore, the optimal reaction time is 18-24 h. When the separation factor reaches 50, the permeation flux of nitrogen gas is 3.1×10 -6 mol / (m 2 ·s·Pa), which is 10-15 times the flux of current silicone rubber-based organic gas separation membranes and more than 30 times that of imported polyimide hydrogen gas separation membranes.
[0260] [Example 38] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water are mixed in a molar ratio of 400:1:1:0.01 and thoroughly stirred to obtain a solution necessary for producing a MOFs membrane.
[0261] (2) Pretreatment of the base film (a) Polyacrylic acid having a mass concentration of 1000 mg / L, partially hydrolyzed polyacrylic acid, polyvinyl alcohol, and zirconium tetrachloride are mixed in a molar ratio of 2:1, and stirred for 1 hour to obtain a post-reaction solution.
[0262] (b) A polypropylene hollow fiber substrate having a pore size of 500 nm was washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) was 1 m 2 The solution produced in (a) is applied to the surface of the dried base film so that the amount of zirconium atoms is 1 / L (i.e., 1 L of the manufacturing solution described in step (a) is applied to a film with a surface of 1 square meter), and then dried, thereby attaching a certain amount of zirconium atoms to the surface of the base film.
[0263] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1)The pretreated base film is immersed in the MOFs production solution described in 2. above to obtain a first mixture, which is protected by introducing nitrogen gas, and an in-situ growth reaction is carried out at 120°C for 24 hours to obtain a separation membrane.
[0264] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0265] (5) Mixing the MOFs organic gas separation membrane prepared in step (4) with a solution containing N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water to obtain a second mixture, in which the molar ratio of N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water is 400:1:1:0.01, and the ratio of the membrane surface area to the solution containing N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water is 0.5 m 2 / L.
[0266] (6) The second mixture obtained in step (5) is heated and reacted at 120° C. for 12 hours to obtain a separation membrane.
[0267] (7) The separation membrane obtained in step (6) is washed to obtain a MOFs organic gas separation membrane.
[0268] The performance test data for this membrane is that the nitrogen gas flux at 0.1 MPa is 3.120 x 10 -6 mol / (m 2 ·s·Pa), whereas the flux of propylene gas is 0.089×10 -6 mol / (m 2 s·Pa), and the nitrogen gas / propylene separation factor is 35.05.
[0269] [Example 39] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water are mixed in a molar ratio of 400:1:1:0.01 and thoroughly stirred to obtain a solution necessary for producing a MOFs membrane.
[0270] (2) Pretreatment of the base film (a) Polyacrylic acid having a mass concentration of 1000 mg / L, partially hydrolyzed polyacrylic acid, polyvinyl alcohol, and zirconium tetrachloride are mixed in a molar ratio of 2:1, and stirred for 1 hour to obtain a post-reaction solution.
[0271] (b) A polypropylene hollow fiber substrate having a pore size of 500 nm was washed with water, washed with ethanol and dried, after which the ratio of the surface area of the substrate to the solution described in (a) was 1 m 2 The solution produced in (a) is applied to the surface of the dried base film so that the amount of zirconium atoms is 1 / L (i.e., 1 L of the manufacturing solution described in step (a) is applied to a film with a surface of 1 square meter), and then dried, thereby attaching a certain amount of zirconium atoms to the surface of the base film.
[0272] (3) The ratio of the surface area of the base film after pretreatment to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1) The pretreated base film is immersed in the MOFs production solution described in 2. above to obtain a first mixture, which is protected by introducing nitrogen gas, and an in-situ growth reaction is carried out at 120°C for 24 hours to obtain a separation membrane.
[0273] (4) The separation membrane obtained in step (3) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0274] (5) Mixing the MOFs organic gas separation membrane prepared in step (4) with a solution containing N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water to obtain a second mixture, in which the molar ratio of N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water is 400:1:1:0.01, and the ratio of the membrane surface area to the solution containing N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water is 0.5 m 2 / L.
[0275] (6) The second mixture obtained in step (5) is heated and reacted at 120° C. for 12 hours to obtain a separation membrane.
[0276] (7) Siloxane Coating: Mix room temperature hydroxysilane, tetraethyl orthosilicate, and n-hexane in a ratio of 1:0.2:8.8, dissolve after 24 h high speed stirring, add 0.01% dibutyltin dilaurate, and perform pre-crosslinking for 5 h to obtain a silane coating solution with a viscosity of 100 mPa·s. Next, immerse the MOFs organic gas separation membrane produced in step (6) in the silane coating solution, leave it for 100 s, then remove it, and the thickness of the coating solution is 5-10 microns.
[0277] (8) Thermal crosslinking: The coated organic gas separation membrane is thermally crosslinked at 80°C for 1 hour to finally obtain an organic gas separation membrane with a three-layer structure.
[0278] The performance test data for this membrane is that the nitrogen gas flux at 0.1 MPa is 1.086 x 10 -7 mol / (m 2 ·s·Pa), whereas the propylene gas flux is 0.03298×10 -7 mol / (m 2 s·Pa), indicating that the nitrogen gas / propylene separation factor is 32.92.
[0279] [Comparative Example 1] (1) Preparation of precursor solution Dissolve 0.42 g of zirconium chloride and 0.30 g of terephthalic acid in 67.5 mL of N,N-dimethylformamide (DMF), add 32 μL of deionized water, employ stirring and ultrasonication to fully dissolve the reagents, and transfer the clear precursor solution into a hydrothermal kettle.
[0280] (2) Heat treatment A polyvinylidene fluoride (PVDF) hollow fiber membrane is immersed vertically in the precursor solution prepared in a fixed frame and heat-treated for 72 hours under a constant temperature condition of 120°C. During the heat treatment, all of the hollow fiber membrane is dissolved in the precursor solution, and the preparation of the separation membrane cannot be completed.
[0281] The state of the undercoat film and the solution after the reaction is shown in FIG.
[0282] [Comparative Example 2] (1) Precursor solutions required for producing MOFs membranes This is the same as in Example 1.
[0283] (2) Pretreatment of the base film (a) Same as Example 1.
[0284] (b) A polyvinylidene fluoride (PVDF) membrane with a pore size of 500 nm is used, and the other properties are the same as those in Example 1. Heat treatment is performed under a constant temperature condition of 120°C for 72 hours. During the heat treatment, the hollow fiber membrane is dissolved in the precursor solution, and the preparation of the separation membrane cannot be further completed.
[0285] The state of the undercoat film and the solution after the reaction is shown in FIG.
[0286] [Comparative Example 3] (1) Preparation of precursor solution Dissolve 0.42 g of zirconium chloride and 0.30 g of terephthalic acid in 67.5 mL of N,N-dimethylformamide (DMF), add 32 μL of deionized water, employ stirring and ultrasonication to fully dissolve the reagents, and transfer the clear precursor solution into a hydrothermal kettle.
[0287] (2) Heat treatment A polypropylene hollow fiber substrate membrane with a pore size of 500 nm is immersed vertically in the precursor solution prepared in a fixed frame, and heat-treated at a constant temperature of 120°C for 72 hours. After the heat treatment is completed, it is allowed to cool naturally.
[0288] (3) Ultrasonic treatment Obtained The film is taken out and subjected to ultrasonic treatment for 5 s to remove particles with low binding strength, thereby obtaining a substrate with seed crystals.
[0289] (4) Formation of a continuous film The substrate with deposited seed crystals is heat treated twice in the same manner as in (2) to obtain a continuous film, which is first washed with DMF and then with methanol and dried at room temperature.
[0290] The electron microscope image of the surface of the produced membrane is shown in Figure 8. As can be seen from Figure 8, each octahedral structure in the MOFs functional layer of the produced membrane exists independently of each other, and no embedded structure is formed.
[0291] [Comparative Example 4] (1) Solutions required for producing MOFs membranes N-methylpyrrolidone, terephthalic acid, zirconium tetrachloride and pure water are mixed in a molar ratio of 400:1:1:0.01 and thoroughly stirred to obtain a solution necessary for producing a MOFs membrane.
[0292] (2) A polypropylene hollow fiber substrate with a pore size of 500 nm is washed with water, washed with ethanol and dried, and then the ratio of the surface area of the substrate to the solution described in (1) is 1 m 2 / L (i.e., a membrane with a surface area of 1 square meter is used for a step of 1 L ( 1) The first mixture is obtained, and nitrogen gas is introduced for protection. An in-situ growth reaction is carried out at 120°C for 24 hours to obtain a separation membrane.
[0293] (3) The separation membrane obtained in step (2) is taken out, and the unreacted monomer and solvent on the membrane surface are washed off to obtain a MOFs organic gas separation membrane.
[0294] (4) The separation membrane obtained in step (3) is washed to obtain a MOFs organic gas separation membrane.
[0295] The electron microscope image of the surface of the produced film is shown in Figure 9. As can be seen from Figure 9, when the base film is not pretreated, several discontinuous crystals adhere to the base film, and the crystals are composed of multiple octahedrons aggregated together, and no continuous structure is formed.
[0296] Although the present invention has been described with reference to any limiting and exemplary embodiments, it should be understood that the words used herein are descriptive and interpretive words, and not limiting words. The present invention can be modified within the scope of the claims of the present invention as specified, and can be modified without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials and examples, it is not meant that the present invention is limited to the specific examples disclosed therein, but on the contrary, the present invention can be extended to all other methods and applications having the same functions.
[0297] BRIEF DESCRIPTION OF THE DRAWINGS 1. Purge gas 2. Gas supply 3. Temperature Sensor 4. Humidity Sensor 5.Membrane module 6. Pressure gauge 7. Gas chromatograph 8. Soap film flowmeter
Claims
1. A metal-organic framework material separation film, comprising: an undercoat film; and a metal-organic framework material functional layer, the metal-organic framework material functional layer comprising a plurality of mutually embedded polyhedron structures; The polyhedrons are composed of a plurality of crystal lattices, and two adjacent polyhedrons in the mutually embedded polyhedral structure share a crystal lattice, and / or the distance between the centers of the two adjacent polyhedrons is smaller than the average length L of the two adjacent polyhedrons; the crystal lattice is composed of metal atoms and organic ligands, the metal atoms being selected from zirconium atoms, niobium atoms, molybdenum atoms, or cobalt atoms, and the organic ligands being selected from terephthalic acid and / or nitroterephthalic acid; The undercoat film is one or more selected from a polypropylene film, a polyethylene film, a polyvinyl chloride film, and a polytetrafluoroethylene film.
2. A separation membrane as described in claim 1, characterized in that two adjacent polyhedrons in the mutually embedded polyhedral structure share a crystal lattice and / or the distance between the centers of the two adjacent polyhedrons is less than 0.95L.
3. A separation membrane as described in claim 2, characterized in that two adjacent polyhedrons in the mutually embedded polyhedral structure share a crystal lattice and / or the distance between the centers of the two adjacent polyhedrons is 0.2-0.9L.
4. The separation membrane of claim 1, wherein at least 20% of the polyhedra in the metal-organic framework material functional layer are embedded in each other.
5. The separation membrane according to claim 4, characterized in that at least 50% of the polyhedrons in the metal-organic framework material functional layer are embedded in each other.
6. The separation membrane according to claim 5, characterized in that at least 80% of the polyhedrons in the metal-organic framework material functional layer are embedded in each other.
7. The polyhedron includes a hexahedron and / or an octahedron, and 2. The membrane according to claim 1, wherein the length of the polyhedron is 50-2000 nm.
8. The separation membrane according to claim 7, wherein the length of the hexahedrons is 50-1000 nm, and the proportion of the hexahedrons having a length of 400-600 nm is 50-80%.
9. The membrane according to claim 7, wherein the length of the octahedrons is 200-2000 nm, and the proportion of octahedra having a length of 800-1200 nm is 60-80%.
10. The metal-organic framework material functional layer has an average pore size of 0.1-2.0 nm; and / or 2. The separator according to claim 1, wherein the thickness of the metal-organic framework material functional layer is 200-5000 nm.
11. The separation membrane according to claim 1, characterized in that the pore size of the base membrane is 10-10,000 nm.
12. The separation membrane described in claim 11, characterized in that the pore size of the base membrane is 200-1000 nm.
13. The separation membrane according to any one of claims 1 to 12, further comprising an organosilicon layer located on the surface of the metal-organic framework material functional layer.
Citation Information
Patent Citations
Preparation method of high dispersion metal-organic framework (MOF) / organic hybrid priority alcohol through composite membrane
CN104001426A
Method for performing induced synthesis on MOFs (metal-organic frameworks) membrane by implanting homologous metal oxide particles into surface of macroporous carrier by virtue of swabbing process
CN104437116A
Composite zeolite membrane, and preparation method and application thereof
CN106278368A
Method for preparing metal-organic framework UiO-66 series membranes and separating methanol / methyl tert-butyl ether mixture
CN106492651A
Method for improving the gas separation performance of supported MOF membrane by utilizing polymer coating
CN108939958A